Factors affecting adherence to lipid-lowering drugs: a scoping review - Said, Abdul Hadi; Abd Rahim, Ikhlas Solehah; Mohamad Zaini, Nur Najihah; Saiful Nizam, Nureena Imani (Oman Medical Specialty Board, 2023)
Objectives: Dyslipidemia is an important risk factor for cardiovascular disease. In developed countries, only 50% of patients with chronic illness adhere to their long-term therapy. This article aimed to review the factors affecting adherence to lipid-lowering drugs (LLDs). Methods: The searched articles were selected based on the available keywords in the title and abstract with the publication restricted between January 2010 and September 2020. Articles generated from the databases must fulfill both inclusion and exclusion criteria in the present systematic review. Our initial search retrieved 221 literature reviews. After excluding articles with irrelevant topics, a total of 23 articles were chosen for this current review. Results: The factors were classified based on three main factors: patient-related, medication-related, and healthcare workers-related factors. For patient-related factors, gender, age, number of family members, education level, post-hospitalization, comorbidities and cardiovascular disease risk, followup status, occupation, socio-economy, insurance, perception, ethnicity, and health plan were among the factors affecting adherence to LLDs. As for medication-related factors, timing, polypharmacy, duration of treatment, generic medication, intensity of medication, side effects, initiating dose, packaging, drug dosing, and type of drugs were revealed as contributing factors. In the light of healthcare workers, related factors shown were counseling, medication optimization, type of provider, and location of the hospital. Conclusions: Recommendations to improve adherence include educating patients on the disease itself and the importance of the treatment, modification of the dosing, timing and type of LLDs, and effective consultations by healthcare workers. Further studies need to be done in Malaysia as there is inadequate research on this topic.